New species of osmundaceous fertile leaves from the upper Triassic of Argentina - Coturel, Eliana Paula; Bodnar, Josefina; Morel, Eduardo Manuel; Ganuza, Daniel Gustavo; Sagasti, Ana Julia; Beltrán, Marisol (Acta Palaeobotanica)
A new species of Osmundopsis Harris is described based on several impression-compression fossils from the upper section of the Potrerillos Formation (Uspallata Group) at Cerro Cacheuta Hill, Mendoza Province, Argentina. Osmundopsis zunigai sp. Nov. is characterized by having fertile pinnae with a slender striate rachis, bearing widely separate, opposite to subopposite short falcate pinnules with an entire margin, rounded apex, and a partially reduced lamina. The pinnules bear sporangia loosely disposed in clusters of four or five on the abaxial side. The sporangia are wedge-to heart-shaped, shortly stalked, with cells of the apical region thickened, and have a vertical dehiscence slit. The spores are trilete and laevigate. This is the first record of Osmundopsis in the Triassic of Argentina. The mutual occurrence or co-preservation of Osmundopsis zunigai sp. Nov. with sterile fronds of Cladophlebis kurtzi suggests the possibility that these species formed part of a dimorphic bipinnate frond. The diversity and geographic extent of fertile leaves of the Osmunda lineage in the early Late Triassic, with records in South Africa and Antarctica and now with this new taxon, support the idea of a moist mesothermal climatic belt in southern Gondwana. Fil: Coturel, Eliana Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Área Paleobotánica; Argentina Fil: Bodnar, Josefina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Área Paleobotánica; Argentina Fil: Morel, Eduardo Manuel. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Área Paleobotánica; Argentina. Provincia de Buenos Aires. Gobernación. Comisión de Investigaciones Científicas; Argentina Fil: Ganuza, Daniel Gustavo. Universidad Nacional de ...